Brinkley & Dyer, Eds., The American Presidency - Akemon, Scott (Teaching History: A Journal of Methods, 2007)
Authors and editors Alan Brinkley and Davis Dyer have woven the interpretive essays of thirty-nine scholars along with their own into a work that covers the abbreviated stories of the forty-two chief executives and how their tenure in office has collectively changed the institution of the presidency. This elite group of historians, which includes Jean H. Baker, Robert Dallek, Michael Kazin, Drew R. McCoy, Roger Morris, and Alan Taylor, offer a variety of perspectives along with some new insights that keeps The American Presidency fresh. As a collection of quality narratives, this work is of high value to a vast audience.